Simian immunodeficiency virus transiently increases brain temperature in rhesus monkeys: detection with magnetic resonance spectroscopy thermometry. Issue 5 (16th January 2019) - Mintzopoulos, Dionyssios; Ratai, Eva‐Maria; He, Julian; Gonzalez, Ramon Gilberto; Kaufman, Marc J.
Abstract : Purpose: To evaluate brain temperature effects of early simian immunodeficiency virus (SIV) infection in rhesus macaques using proton magnetic resonance spectroscopy (MRS) thermometry (MRSt) and to determine whether temperature correlates with brain choline or myo‐inositol levels. Methods: Brain temperature was retrospectively determined in serial MRS scans that had been acquired at baseline and at 2 and 4 weeks post‐SIV infection (wpi) in 16 monkeys by calculating the chemical shift difference between N‐acetylaspartate (NAA) and water peaks in sequentially acquired water‐suppressed and unsuppressed point‐resolved spectroscopy (PRESS) spectra. Frontal and parietal cortex, basal ganglia, and white matter spectra were analyzed. Results: At 2 wpi, brain and rectal temperatures increased relative to baseline and normalized at 4 wpi. Brain temperatures correlated with choline levels in several brain areas, but not with myo‐inositol levels. Conclusion: These data indicate that SIV transiently increases brain temperature soon after infection and that temperature is correlated with transient changes in choline levels. Given that choline levels are associated with brain inflammation in SIV‐infected monkeys, our findings suggest that the SIV‐induced temperature increase reflects brain inflammation. We conclude that MRSt may be informative in human immunodeficiency virus models and may be useful for assessing effects of treatments that reduce inflammation. This study also illustrates that existing MRS data sets containing unsuppressed water spectra can be used to measure tissue temperature, an important physiological parameter.